Obesity Leads to Elevated Level of Circulating Cell-Free DNA - Atif Amin, Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Tengku Muhammad Ariff, Raja Hussin (2018)
With the steadily growing number of studies in the issues related to obesity research, it is proven, that obesity might be related to wide number of body disorders, some of these disorders have been already studied and investigated, and some still needed more investigations, which has opened new horizons to unlimite hypotheses about involvement of obesity in many physiological disorders. In the current opinion, we hypothesized to the conclusion that there is a correlation between obesity severity and elevated cfDNA levels in the circulation. This correlation is based on free radicals and oxidative stress hypothesis of cellular and molecular damage in cell injury, which in turn leads to a disorder in the whole body and enhances the inflammatory status.